Pengaruh Komitmen Organisasional, Sistem Informasi Akuntansi, dan Peran Audit Internal Terhadap Kualitas Laporan Keuangan - Frasca Ardy Nugroho; Widhy Setyowati (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2019)
The purpose of this study was to analyze the effect of organizational commitment, accounting information systems, and internal audits on the quality of the financial statements of the Tegal Regency. There are 125 employees of the Tegal Regency government finance department were taken as a sample by purposive sampling. The data used in this study were obtained through a questionnaire. Multiple linear regression analysis has been used to analyze the data in this study. The results showed that organizational commitment, accounting information systems, internal audits significantly influenced the quality of the Tegal Regency Government's financial statements in a positive direction. Some suggestions were proposed such as the need to increase the number of computers, ease of accessing the results of audit reports and increased independence in conducting audits. This is intended to improve the quality of financial statements